THE LEGAL ANALYSIS AND THE IMPACT OF NOT DELETING OLD DATA IN INFORMATION SYSTEMS OF CREDIT PROGRAM ON KUR FINANCING FOR MICRO, SMALL AND MEDIUM ENTERPRISES - Andi Aina Ilmih; A. Zulkarnain; Kami Hartono (Jurnal Pembaharuan Hukum, 2022)
This study focuses on the importance of deleting data from the Program Credit Information System for People's Business Credit for MSME customers who have paid off their financing and re-apply for People's Business Credit facilities financing facility assistance from the government, by analyzing legal policies that regulate People's Business Credit facilities financing through Program Credit Information System in Indonesia and knowing the impact of not deleting Program Credit Information System data on People's Business Credit financing for MSME customers in Semarang Syari’ah Banking. This research uses empirical legal research method, with descriptive-analytical method. Based on the research that has been done, the legal arrangements and policies for People's Business Credit financing through Program Credit Information System in Islamic Banking are regulated in the Coordinating Minister for Economic Affairs Regulation Number 2 of 2021 concerning the Second Amendment to the Coordinating Minister for Economic Affairs Regulations Number 8 of 2019 concerning Guidelines for the Implementation of People's Business Credit; and the Coordinating Minister for Economic Affairs Regulations Number 3 of 2021 concerning the Fourth Amendment to the Coordinating Minister for Economic Affairs Regulations Number 6 of 2020 concerning Special Treatment of People's Business Credit facilities during the Covid-19 Pandemic. The impact of not deleting Program Credit Information System data for People's Business Credit financing customers for MSME actors in Islamic Banking includes positive and negative impacts. The positive impact is the existence of a data base for MSME actors as customers of People's Business Credit Financing at Program Credit Information System, becoming a guideline or benchmark for banks in distributing People's Business Credit facilities and the negative impact is the existence of a People's Business Credit financing database for MSME actors who pay off their financing if it is still listed in Program Credit Information System as a digital track record of People's Business Credit financing for SMEs in other Islamic banking and can be an obstacle/obstacle in obtaining People's Business Credit facility assistance from the government.